Occurrence of a new piscine tapeworm Senga govindii in Mastacembelus armatus (Lacepede, 1800) from Sina kolegoan Dam - Jadhav, Swati; Borde, Sunita; Jadhav, Dilip; Humbe, Atul (Journal of Experimental Sciences, 2012)
The present communication deals with the occurrence of a new mammalian tapeworm Senga (Dollfus, 1934) govindii Sp. Nov. from Mastacembelus armatus (Lacepede, 1800) in Sina kolegoan Dam Osmanabad Dist.(M.S.). It comes closer to all the known species of the genus Senga but differs from all the known species of the genus in having in the shape and shape of the scolex, 45-50 hooks, mature segment three times broader than long, total number and arrangement of testes, position of cirrus pouch, vitellaria granular, Ovary is bilobed.